Behavioral Changes in Patients with Multiple Sclerosis - Heldner, Mirjam R.; Kaufmann-Ezra, Sigal; Gutbrod, Klemens; Bernasconi, Corrado; Bigi, Sandra; Blatter, Verena; Mattle, Heinrich P.; Müri, René M.; Verma, Rajeev K.; Kamm, Christian P. (Frontiers in Neurology, 2017)
Background: Behavioral changes are common in patients with multiple sclerosis (MS), however not as readily recognized as cognitive impairments. Objective: The aim of this study was to analyze behavioral changes and its relation to disease characteristics, disability and cognitive impairments in patients with MS. Method: Single center cross-sectional study. A detailed neuropsychological examination including the Frontal Systems Behavior Scale (FrSBe), the Beck depression inventory (BDI) and the Wuerzburg Fatigue Inventory for Multiple Sclerosis test (WEIMuS) was performed. FrSBe results were correlated with disease characteristics, disability and cognitive assessments. Results: 66 patients were enrolled (mean age: 43.4 years; disease duration: 9.3 years; EDSS: 3.0). Up to one third of patients showed behavioral changes in at least one domain or the total score of the FrSBe. Patients were mildly affected with regard to cognitive functioning. Consistent correlation was found between behavioral changes and fatigue (WEIMuS) and depressive symptomson (BDI), but not with disease characteristics, disability or cognitive functions. There was an increase of behavioral changes on all FrSBe scales in the current status compared to the retrospectively rated status before disease onset. Self- and family ratings with regard to current behavioral changes were similar. Conclusions: Behavioral changes are common in otherwise mildly affected MS patients with up to one third being affected. In this patient cohort, behavioral changes occur largely independent of disease characteristics, physical disability and cognitive functioning but correlate both with fatigue and depressive symptomson. They should therefore be tested specifically.